The Climatic Regions and Desertification Level for Diyala River Basin in Iraq - Al-Tamimi, Omer Sabah; Gamel, Shaima Abd Algalil (Iraqi Journal of Science, 2022)
The current study a accounts for the climate of the Diyala River Basin in Iraq where the climate is assessed depending on the most wellknown climatic classification. According to these classifications, it has been discovered that the area is located under Three climatic zones. The first zone is the semi humid or moderate, which covers the northern parts of the area. The second zone is the semi –dry climate which spreads over the middle part of the region. The third one, it extends over the southern parts and it is described as being dry .some maps were drawn to show the depth of rain fall for two successive periods. These maps indicate increase in the area of lands affected by the dry climate on account of the lands that used to lie under the effect of the semi – dry climate.